ELECTRIFICATION HISTORY OF UZBEKISTAN IN SCIENTIFIC LITERATURES (American Journal of Research in Humanities and Social Sciences, 2023)
Necessary conditions have been created for strengthening the economic relations between the electric energy system, industry and social spheres, increasing their technical potential. Today, it is impossible to imagine any sphere of society's life without electricity. In the 21st century, the steady increase in demand for mineral resources for the purpose of energy production is the reason for the intensification of geopolitical rivalries.